Setting the Operational Framework for Producing Inflation Forecasts - Kisinbay, Turgut (IMF Working Papers; Working Paper, 2006)
How should a central bank organize itself to produce the best possible inflation forecast? This paper discusses elements for building a comprehensive platform for an inflation forecasting framework. It describes the exercise of forecasting inflation as a production process, which induces a strict discipline concerning data management, information gathering, the use of a suitable statistical apparatus, and the exercise of sound communication strategies to reinforce reputation and credibility. It becomes critical how a central bank organizes itself to produce relevant macroeconomic forecasts, with special consideration to product design, the essential requirements needed in the forecasting process, and key related organizational issues. In addition, the paper proposes to factor into the process the authorities' policy responses to previous inflation forecasts in order to be consistent with the spirit of the inflation targeting framework.